Pengaruh Konsentrasi Tween 80 Pada Sakarifikasi Dan Fermentasi Serentak Pati Sorgum Menjadi Bioetanol - Ajma Nouri; Chairul Chairul; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The growing energy needs of Fuel (BBM) in the world are experiencing the limitations of the natural resources of raw materials in the form of fossil fuels are declining. To meet the needs of fuel need to be developed for non-fossil fuels. One type of vegetable fuel (BBN) is bioetanol. Raw materials that are potentially as bioetanol one is sweet sorghum (Sorghum bicolor l. Moench). Starch sorghum can be converted into glucose and then by using the help of microorganisms are converted into bioetanol. The methods used in this research is the process of sakarifikasi and the fermentation is done simultaneously (SSF) in 2-Litre fermenters. Sampling is conducted during the process of hidrolisa by using StargenTM enzyme and fermentation at specific time intervals to analyze levels of ethanol and sugar levels. Test your sugar levels reduction done by the method of Nelson-Somogy, alcohol concentration testing using the tool alkoholmeter. The purpose of this study was to determine the influence of the concentrations of Tween 80 and the fermentation time against levels of ethanol produced. Starch fermentation process conditions of sorghum with the variation of the concentrations of Tween 80 (0.5%; 1%; 0.9%; 2% and 2.5%) at each sampling time (36; 24; 48; 60, 72 and 96 h). The fermentation process takes place in the anaerobic conditions of operation pH (4.5) speed of 200 rpm and pengadukkan at room temperature. The best fermented indicated on condition of addition of enzyme concentration of 2.5%, the fermentation time 72 hours with the resulting ethanol concentration of 8% (v/v).Keywords: Bioetanol, Fermentation, starch sorghum, StargenTM 002, Tween 80